Synthesis and Characterization of Coir and Luffa Cylindrica filled with CaCo3 hybrid composites - Mohana Krishnudu, Doni; Sreeramulu, Dowluru; Reddy, P Venkateshwar (International Journal of Integrated Engineering, 2019)
Usage of natural fiber hybrid composites is increasing in the present days because of its eco-friendly and biodegradable nature. Coir fibers were extracted from the plant bark and Luffa Cylindrical were extracted from the vegetable fruit. Later both the fibers were treated with alkaline (5% NaoH) solution to remove the greasy nature over the surface. Â In the present study, composites were fabricated by using Coir and Luffa Cylindrica along with CaCo3 natural fiber hybrid composites. Each composite is tested for tensile, flexural and impact tests as per the ASTM standards. The composite specimens were characterized using Fourier transform infrared spectrophotometry (FTIR), scanning electron microscopy (SEM) and thermo-gravimetric analysis (TGA/DTA). SEM illustrated a good bonding between matrix and fibers. TGA illustrated the amount of residue leftover in the composite. FTIR illustrated which compounds are present in the composite.